2018
DOI: 10.1017/s1352465818000036
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful Ways of Understanding and Measuring Change for People with Borderline Personality Disorder: A Thematic Analysis

Abstract: This investigation highlights the complex nature of measuring change in people who have received a BPD diagnosis. Further research is needed to develop meaningful ways of measuring change according to the needs and priorities of people with BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Thus, the findings of this study highlight the equal importance of concurrently addressing both core emotional issues within therapy, as well as facilitating social connection and support when considering treatment and recovery options for people with BPD and co-occurring impulse disorders. These findings concur with recent qualitative explorations of BPD recovery (Donald et al , 2017a, 2017b; Katsakou and Pistrang, 2017; Castillo et al , 2013; Gillard et al , 2015; Lariviere et al , 2015; McCusker et al , 2018) as well as with broader attempts to conceptualise the recovery trajectories of people with SUDs and mental health difficulties within one unifying framework. For instance, the US Department of Substance Abuse and Mental Health Services (SAMHSA, 2006) has published a working definition of recovery that encompasses ten guiding principles, all of which are arguably reflected within the themes presented in the current study: hope (hope and purpose), self-determination (agency and autonomy), relationships, social and peer support, respect (societal acceptance and fostering self-acceptance: addressing stigma), taking a holistic approach (self-care, occupation, finances, housing, etc.)…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the findings of this study highlight the equal importance of concurrently addressing both core emotional issues within therapy, as well as facilitating social connection and support when considering treatment and recovery options for people with BPD and co-occurring impulse disorders. These findings concur with recent qualitative explorations of BPD recovery (Donald et al , 2017a, 2017b; Katsakou and Pistrang, 2017; Castillo et al , 2013; Gillard et al , 2015; Lariviere et al , 2015; McCusker et al , 2018) as well as with broader attempts to conceptualise the recovery trajectories of people with SUDs and mental health difficulties within one unifying framework. For instance, the US Department of Substance Abuse and Mental Health Services (SAMHSA, 2006) has published a working definition of recovery that encompasses ten guiding principles, all of which are arguably reflected within the themes presented in the current study: hope (hope and purpose), self-determination (agency and autonomy), relationships, social and peer support, respect (societal acceptance and fostering self-acceptance: addressing stigma), taking a holistic approach (self-care, occupation, finances, housing, etc.)…”
Section: Discussionsupporting
confidence: 88%
“…For further refinement of treatment for personality disorder, investigation of factors promoting or challenging the therapeutic process are central. In this regard, user perspectives and qualitative exploration of first-hand accounts are valuable resources (Little et al, 2018; McCusker, Turner, Pike, & Startup, 2018; Montgomery & Donnelly, 2014). It has been suggested that the introductory, psychoeducational group may contribute to the low drop-out rates reported in MBT (Kvarstein et al, 2014).…”
mentioning
confidence: 99%
“…Only 13% of the participants who completed treatment could be considered recovered in line with IAPT criteria. Still, the aim of STEPPS-EI is not primarily to address symptoms of depression or anxiety but rather emotional intensity, hence it would be misguided to evaluate the feasibility of STEPPS-EI based solely on these recovery rates (McCusker et al, 2018).…”
Section: Discussionmentioning
confidence: 99%